Food and nutrition in the prevention of atherosclerosis - Izabela Kamila Wojarska; Małgorzata Białek; Hubert Wojarski (Kazimierz Wielki University, 2018)
Cardiovascular disease is the most frequent cause of hospitalization (15%) and death (46%) in Poland, as well as worldwide (31%), by reason of strenuous activity in the field of preventative healthcare in all age groups has to be taken. Preventative nutrition of atherosclerosis predicts mostly intake restriction of food containing: fatty acids, cholesterol, salt, monosaccharides and animal protein, while increasing intake of vitamins, minerals, fiber and antioxidant substances. Eating habits and nutritional status of women who are planning pregnancy have a crucial impact on its course, development of the fetus and children's health in later years of their life. For all of cardiac patients well balanced diet is advised. In preventative care of Cardiovascular Disease it is advised to apply the diet given by a certified dietician and adjusted to fit patient's needs. It is to remember, that besides a good diet, an important therapeutic factor of the patients with atherosclerosis is physical activity. Cardiovascular disease is a serious concern in Poland, as well as worldwide. Eating habits are playing a big role in pathogenesis and prevention of atherosclerosis.